Providing Social Protection and Livelihood Support During Post-Earthquake Recovery - Vishwanath, Tara; Yu, Xiaoqing (World Bank, Washington, DC, 2012)
Providing basic income and employment support is an essential component of the government efforts to rebuild the province of Sichuan from the devastation caused by the earthquake. The primary objective of such policies is to protect the most vulnerable households in the affected communities. These policies can also have benefits in terms of rejuvenating local economic activities by creating purchasing power in affected areas, as well as rebuilding severely damaged basic infrastructure by integrating select reconstruction activities with social protection programs. This note focuses on two main approaches: cash transfer and public works programs. After the South Asia earthquake in 2005, Pakistan used a cash transfer program to protect the vulnerable and help regenerate local economies. To illustrate how a public works program can be a flexible instrument for providing short-term income support while at the same time contributing to the recovery of essential public infrastructure, the experience of several countries is introduced. Building on these country experiences, the note discusses key lessons relevant for China.